1998
DOI: 10.1007/s005200050177
|View full text |Cite
|
Sign up to set email alerts
|

Constipation in advanced cancer patients

Abstract: Constipation is a frequent, distressing, and underestimated complication in patients with advanced cancer. It may develop from general disturbances that may or may not be cancer related, but the use of opioids is one of the main causes in this population. Opioids affect the intestine by reducing motility and secretions and by increasing fluid absorption and blood flow. Untreated constipation may lead to several complications. Effective management of constipation starts with a careful assessment of the patient,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
87
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(90 citation statements)
references
References 42 publications
1
87
0
2
Order By: Relevance
“…Constipation in advanced cancer patients shares some of these causes, but also has local causes, e.g., gut motility or pelvic floor dysfunction (29,30). Diarrhoea, in contrast, is commonly associated with some treatments and is largely an acute symptom in advanced cancer patients (31).…”
Section: Discussionmentioning
confidence: 99%
“…Constipation in advanced cancer patients shares some of these causes, but also has local causes, e.g., gut motility or pelvic floor dysfunction (29,30). Diarrhoea, in contrast, is commonly associated with some treatments and is largely an acute symptom in advanced cancer patients (31).…”
Section: Discussionmentioning
confidence: 99%
“…However, it induces severe constipation, causing an obvious reduction in quality of life (QOL) (1). In a previous examination of records of cancer patients at a hospital (Chiba Rosai Hospital, Chiba), we found that 64.9% of patients who take morphine-containing drugs suffer from severe constipation (2).…”
mentioning
confidence: 99%
“…The gastroenterologic use of opioids has recently been extended to the alleviation of diarrhea and visceral pain in irritable bowel syndrome (Corazziari, 1999). In addition to their therapeutic effects, opioids produce severe constipation during their prolonged use in pain management (Mancini and Bruera, 1998). The actions of opioids are thought to stem from their ability to decrease both intestinal propulsion and mucosal anion secretion (De Luca and Coupar, 1996).…”
mentioning
confidence: 99%